High and middle school science, mathematics and computer science teachers' perceptions and attitudes about teacher colaboration - Öztekin, Utku. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Collaborative working skills is one of the most important dimensions for improv ing instructional quality through STEM and 21st century skills. Based on an action research guided by explanatory sequential mixed-method design, this research sought to investigate teachers’ perceptions and attitudes for teacher collaboration in Profes sional Learning Com- munity (PLC) framework. The study focusses on descriptive questions with contextual and procedural structures. Data collection is made through online documents for preliminary investigation for research site; Demographic Analysis Teacher Questionnaire (DATQ) to gather information about teachers’ characteristics and attitudes in the school setting, School Professional Staﬀ as Learning Community Questionnaire (SPSLCQ) for contextual analysis and Teacher Collaboration Assess ment Rubric(TCAR) for conceptual analysis; and semi-structured interview for an in-depth understanding of eﬀective collaboration. 33 teachers attended quantitative and 6 teachers attended qualitative part of the research. The ﬁrst major ﬁnding is the diﬀerence between the mean scores for frequencies of using fundamental collabo ration skills (74.50%) and eﬀective collaboration skills (35.12%). Diﬀerences between the contextual and conceptual collaboration scores of high school and middle school teachers are investigated through interviews. Results show that interdisciplinary collab oration oriented planning of middle school administration enhances teacher’s eﬀective collaboration attitude. When the procedural focus of the collaboration is considered, evaluation comes up as the part that is needed to focus on. A collaborative process is ﬁnalized with the end of the action part.
Keywords: Mathematics teachers.; Science teachers.